1994
DOI: 10.1111/j.1471-6402.1994.tb01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Theory And Research With Women: Themes and Variations

Abstract: We look at some of the ways in which feminist theorists and researchers apply new insights to established topics in psychology, as they explore the landscape of the unknown and unspoken in the lives of girls and women. The articles in this special issue present research and reflections by a group of feminist scholars, some of us from the editorial board of the Psychology of Women Quarterly and others from the larger academic community. Each contributor, selecting from a personal interest or expertise, reconcep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 19 publications
0
44
0
1
Order By: Relevance
“…Based on our own review of recent writings on feminist theory and methodology, we found that there seem to be four core principles that are endorsed by feminist social scientists of all theoretical orientations. These core principles, which overlap with those identified by Worell and Etaugh (1994), can be summarized as: (1) the recognition of the validity and importance of women's experiences;…”
Section: Common Features Of Feminist Researchmentioning
confidence: 99%
“…Based on our own review of recent writings on feminist theory and methodology, we found that there seem to be four core principles that are endorsed by feminist social scientists of all theoretical orientations. These core principles, which overlap with those identified by Worell and Etaugh (1994), can be summarized as: (1) the recognition of the validity and importance of women's experiences;…”
Section: Common Features Of Feminist Researchmentioning
confidence: 99%
“…They faulted ex periments' lack of representativeness of natural settings, a feature known as context stripping (i.e., lack of ecological validity; Worell & Etaugh, 1994). Many feminist critics thus advocated data collection in natural settings (e.g., Crawford & Kimmel, 1999;M.…”
Section: F E M I N I S T C R It Ic Is M S O F P S Y C H O L O G Y 'S mentioning
confidence: 98%
“…Feminist psychologists' contributions to scholarship have extended into and shaped all aspects of the discipline, as well as research on the psychology of women, over the past few decades, and feminist scholarship has resulted in significant advances in myriad aspects of theory, research methods, and the study of gender issues in multiple subfields (Kite et al, 2001;O'Connell & Russo, 1991;Worell & Etaugh, 1994). On the other hand, obstacles faced by feminist scholars, including resistance by students and colleagues to the topics studied and approaches taken to study them and practical dilemmas such as publication outlets and lack of available grant funds, remain problematic for career advancement (Benokraitis, 1998;Grossman et al, 1997).…”
Section: Scholarshipmentioning
confidence: 99%